1973
DOI: 10.1113/expphysiol.1973.sp002212
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Frequency During Submaximal Exercise in Young Adults; Relation to Lean Body Mass, Total Body Potassium and Amount of Leg Muscle

Abstract: The cardiac frequency and consumption of oxygen during submaximal exercise, lean body mass, total body potassium, thigh muscle width and an index of thigh muscle volume have been obtained for seventy-nine healthy men and women, ages 18 to 38 yrs, who were not in athletic training but accustomed to taking some exercise. For these subjects, at any specified submaximal rate of consumption of oxygen, the cardiac frequency is negatively correlated with the indices of body muscle which are themselves inter-correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…1). From the regression equation we determined the heart rate at a standard vo, of 1.5 1 min-' (Cotes et al 1973) and following repeat testing, the significance of a shift in the line and a measure of a change in cardiorespiratory fitness was taken as a significant change in the elevation of the regression line (Kappagoda et al 1979). Peak vo, was the oxygen uptake at the highest stage of exercise that the subject could undertake.…”
Section: Exercise Testmentioning
confidence: 99%
See 1 more Smart Citation
“…1). From the regression equation we determined the heart rate at a standard vo, of 1.5 1 min-' (Cotes et al 1973) and following repeat testing, the significance of a shift in the line and a measure of a change in cardiorespiratory fitness was taken as a significant change in the elevation of the regression line (Kappagoda et al 1979). Peak vo, was the oxygen uptake at the highest stage of exercise that the subject could undertake.…”
Section: Exercise Testmentioning
confidence: 99%
“…Furthermore, the programme is relatively simple and considered to be safe. We used submaximal methods for assessing fitness partly also because of safety and acceptability (Cotes, 1993) and partly because of the better reproducibility (Mary, 1987).…”
Section: B L M T I N a N G I A N D R H A I N S W O R T Hmentioning
confidence: 99%
“…Previous studies have shown associations between elevated heart rate (HR) at rest and increased risk of both all-cause and cardiovascular mortality (7,18,21,22,25,26,33). Although HR during submaximal exercise is known to decrease in response to regular endurance training (16,51), its recovery after maximal and submaximal exercise is considered a powerful predictor of mortality (14,15). However, interindividual differences in training-induced changes in HR are considerable.…”
mentioning
confidence: 99%
“…It was considered reasonable to use a fixed reference cardiac frequency of 180 min1 (near maximum for the unfit population) which it was assumed most subjects in a random population could reach under stress if required rather than to apply theoretical age corrections such as Astrand [1960] did to determine maximum heart rate, a procedure which might be unsuitable for a particular population. Oxygen uptake has been expressed in terms of the subject's weight, or, on occasion, allowance has been made for the subject's fat, total body potassium and amount of leg muscle [Cotes, Berry, Burkinshaw, Davies, Hall, Jones and Knibbs, 1973]. This however introduces further variables and if a population's aerobic power is considered before and after a programme of exercise and prescribed diet the result may indicate an apparent increase in aerobic power due simply to a dietary decrease in weight.…”
mentioning
confidence: 99%